PH-Dependent growth of atomic Pd layers on trisoctahedral gold nanoparticles to realize enhanced performance in electrocatalysis and chemical catalysis12. Issue 47 (23rd November 2018) - Song, Yahui; Xiang, Chensheng; Bi, Cuixia; Wu, Chenshuo; He, Hongpeng; Du, Wei; Huang, Lihui; Tian, He; Xia, Haibing
Abstract : Trisoctahedral gold nanoparticles with atomic Pd layers by the pH-dependent growth can be used in catalysis and in situ SERS monitoring. Abstract : In this work, the controlled epitaxial growth of ultrathin Pd shells of a few atomic layers (denoted as n L) on the surfaces of gold nanoparticle (Au NP) cores of different morphologies (trisoctahedral, cubic, and spherical shapes) in the presence of cetyltrimethylammonium chloride (CTAC) was achieved by regulating the pH value of the aqueous CTAC solution and finely tuning the amount of the Pd precursor. It was found that the critical shell thickness for epitaxial Pd growth at the optimal pH value was 4 atomic layers, taking {331}-faceted trisoctahedral (TOH) Au@Pd n L NPs as an example, on the basis of the results of atomic-resolution high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) images. Moreover, the resulting TOH Au@Pd1L NPs (100.9 m 2 g −1, 13.2 A mgPd −1 and 13.1 mA cm −2 ) exhibited excellent electrocatalytic performance and long-term electrocatalytic activity for ethanol oxidation, around 4.8-fold, 66-fold, and 21.8-fold better than commercial Pd/C catalysts (31 m 2 g −1, 0.2 A mgPd −1, and 0.6 mA cm −2 ). Furthermore, the resulting TOH Au@Pd1L NPs not only markedly enhance the chemical catalytic activity for the reduction of 4-nitrophenol (4-NP), but also allow the in situ surface-enhanced Raman spectroscopy (SERS) monitoring of the reaction process of the Pd-catalyzed reduction of 4-NTP. Thus, our work may provide a new way to fabricate core–shell (CS) bimetallic NPs with the merits of both metal outer shells (excellent catalytic performance in electrocatalysis and chemical catalysis) and Au NP cores (reaction process by in situ SERS monitoring).